Improving The Quality Of Education In The 5.0 Era: Quality Control And Quality Improvement Approaches - Susanti, Rahayu; Lengkong, Indira Krisanti; Madhakomala, R (Journal Coaching Education Sports, 2024)
Education in the 5.0 era faces significant challenges in maintaining quality and relevance alongside the development of smart technology and the demand for 21st-century skills. This article analyzes the role of Quality Control (QC) and Quality Improvement (QI) in enhancing education quality through a literature review. The analysis reveals that QC and QI play crucial roles in maintaining quality standards and driving continuous improvement. QC ensures consistent quality monitoring, while QI enables adaptation through technological innovations, such as data analytics and artificial intelligence. The integration of technology into QC and QI provides notable benefits, including real-time monitoring of student performance and personalized learning to improve educational outcomes. However, this implementation faces challenges, including limited infrastructure, low digital literacy among educators, and resistance to change. The synergy between technology and human skills is identified as a key factor in creating an effective and meaningful education process. The article recommends investing in technological infrastructure and educator training, along with policies supporting QC and QI implementation in educational institutions. Further research is necessary to develop more adaptive QC and QI models for various educational contexts and explore the impact of technology-based QC and QI on students' 21st-century skills. These findings aim to provide insights into sustainable strategies for improving education quality in the 5.0 era.